2021
DOI: 10.34198/ejms.7121.123
|View full text |Cite
|
Sign up to set email alerts
|

Strongly log-biconvex Functions and Applications

Abstract: In this paper, we consider some new classes of log-biconvex functions. Several properties of the log-biconvex functions are studied. We also discuss their relations with convex functions. Several interesting results characterizing the log-biconvex functions are obtained. New parallelogram laws are obtained as applications of the strongly log-biconvex functions. Optimality conditions of differentiable strongly log-biconvex are characterized by a class of bivariational inequalities. Results obtained in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We now recall some concepts of biconvex sets and biconvex functions, which are mainly due to Noor et al [21,22,23,24]. Definition 2.1.…”
Section: Preliminaries and Basic Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We now recall some concepts of biconvex sets and biconvex functions, which are mainly due to Noor et al [21,22,23,24]. Definition 2.1.…”
Section: Preliminaries and Basic Resultsmentioning
confidence: 99%
“…We now suggest and analyze some new iterative methods for solving the trifunction bihemivariational inequality (2.1) using the auxiliary principle technique of Glowinski, Lions and Tremolieres [10] without the Bregman distance function as developed by Noor [16][17][18][19][20][21][22][23][24].…”
Section: Collapses To the Methods For Solving The Bivariational Inequalities (22)mentioning
confidence: 99%
See 2 more Smart Citations
“…Log-convex mappings, which include hypergeometric mappings such as Gamma and Beta, are crucial in a number of fields of pure and practical sciences. Strongly logbiconvex mappings were first discussed by Noor and Noor [15], who also looked at their characterization. It is demonstrated that the bivariational inequalities are a novel generalization of the variational inequalities that can be used to describe the optimality conditions of the biconvex mappings.…”
Section: Introductionmentioning
confidence: 99%